PUBLIC SECTOR AND INTELLECTUAL PROPERTY: THE OWNERSHIP OF INTELLECTUAL PROPERTY OF COMPUTER PROGRAM, CREATED AND DEVELOPED OR CUSTOMIZED FOR USE IN THE MANAGEMENT OF THE JUDICIARY (Revista Justiça do Direito, 2015)
In a continental country as Brazil, the questions linked with the public administration gain a monumental proportion. Such is with the use of computer programs, each time more and more used in the essential public management like the Justice. The creation of innovations within the Public Administration is increasingly common, as evidenced mainly through the use of new information technologies. To care the intellectual property of this creations is of strategic importance. Considering intangible assets as an important factor in development, and also a promising source of revenue for the State, a legal and economic treatment appropriate for these matters should be sought.Key-Words: Public Administration, Justice, and Intellectual Property, Software.